1991
DOI: 10.1080/00222349108245785
|View full text |Cite
|
Sign up to set email alerts
|

Observed structural change in poly-n-butyl isocyanate

Abstract: We report a conformational change observed in poly-n-butyl isocyanate (PBIC) dissolved in carbon tetrachloride (CC14) with temperature. This change was detected by measuring the reduced viscosity of the polymer solution with a Zimm-Crothers type viscometer of very low shear rate; we found a reversible jump in reduced viscosity whose amplitude depends on concentration, but its position is only molecular weight dependent. This jump goes from lower to higher values of reduced viscosity when we increase the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The polymers characteristics are listed in Table 3. Dilute solution viscosity and conformation transition studies on the PBIC series utilizing Ubbelohde and Zimm‐Crothers viscometers have been reported by Romo‐Uribe et al 51,52 …”
Section: Methodsmentioning
confidence: 83%
“…The polymers characteristics are listed in Table 3. Dilute solution viscosity and conformation transition studies on the PBIC series utilizing Ubbelohde and Zimm‐Crothers viscometers have been reported by Romo‐Uribe et al 51,52 …”
Section: Methodsmentioning
confidence: 83%
“…Fiber diffraction experiments demonstrated that poly( n -butyl isocyanate) [PBIC] adopts an 8/3 helical conformation in the solid state . Static characterization methods, such as light-scattering, osmotic pressure 7 and electric dichroism measurements, and dynamic characterization methods, such as dielectric, mechanically- or electrically-induced birefringence, and viscometric measurements, demonstrated that poly(alkyl isocyanates) are stiff-chain polymers whose hydrodynamic properties are highly temperature-, solvent-, and molecular-weight-dependent. At lower molecular weights these polymers behave as true rigid rods, while at very high molecular weights they behave as semiflexible chains or “worm-like” polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported an abrupt increase of reduced viscosity as temperature increased. The change of viscosity was associated to a conformation transition as the viscosity is correlated with macromolecular dimensions 29,39 …”
Section: Introductionmentioning
confidence: 99%
“…The chemical formula and the helix conformation are shown in Scheme 1. 30,54 There are reports on conformation transition and order-order transition in poly-n-butyl isocyanate (PBIC) 28,29 and poly-n-hexyl isocyanate (PHIC), 30 respectively. That is, these stiff-chain polymers can exhibit a helix to β-sheet transition where there is a well-ordered molecular multi-bilayer structure of the fully extended polymer chains in the 2 1 conformation with no interdigitation between the side groups of adjacent molecular layers.…”
mentioning
confidence: 99%
See 1 more Smart Citation